2004
DOI: 10.1177/004051750407400307
|View full text |Cite
|
Sign up to set email alerts
|

Neural Networks: An Alternative Solution for Statistically Based Parameter Prediction

Abstract: Over the past years, research has attempted to relate fiber properties with yarn prop erties, and many regression equations have been developed to accomplish this. The complexities of multiple regression equations put limits on their universal acceptance. Neural networks with better nonlinear mapping have also been used to develop such relationships. Our statistical data analysis of a few yarn properties will determine the suitability of neural networks for such textile applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…These were mean square error (mse), training time and correlation coefficient (R 2 ). These are the factors commonly reported by many researchers (Cheng and Adams 1995;Chattopadhyay et al 2004;Desai et al 2004;Majumdar and Majumdar 2004;Majumdar et al 2005;Huang et al 2006a;Ureyen and Gurkan 2008a, b;Mehment 2009). The ELM trained algorithms were trained in a similar manner like the LMBP algorithm, however the training algorithm used was ELM.…”
Section: Designing and Training Of Prediction Modelsmentioning
confidence: 80%
“…These were mean square error (mse), training time and correlation coefficient (R 2 ). These are the factors commonly reported by many researchers (Cheng and Adams 1995;Chattopadhyay et al 2004;Desai et al 2004;Majumdar and Majumdar 2004;Majumdar et al 2005;Huang et al 2006a;Ureyen and Gurkan 2008a, b;Mehment 2009). The ELM trained algorithms were trained in a similar manner like the LMBP algorithm, however the training algorithm used was ELM.…”
Section: Designing and Training Of Prediction Modelsmentioning
confidence: 80%
“…In the field of textiles, artificial neural networks (mostly using back-propagation) have been extensively studied during the last two decades [4][5][6]. In the field of spinning previous research has concentrated on predicting the yarn properties and the spinning process performance using the fiber properties or a combination of fiber properties and machine settings as the input of neural networks [7][8][9][10][11][12]. Back-propagation is a supervised learning technique most frequently used for artificial neural network training.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Dr. J. V. Desai et. el [14] implemented yarn property prediction & showed that single neural structure is unable to predict all the yarn properties with desired accuracy. But with the help of powerful algorithms this conclusion can be discarded.…”
Section: Introductionmentioning
confidence: 99%
“…limited number of yarn properties [9,14]. It is more desirable to find out fiber properties in advance according to customer design yarn properties i.e.…”
mentioning
confidence: 99%